2020
DOI: 10.2196/22523
|View full text |Cite
|
Sign up to set email alerts
|

Adapting an Outpatient Psychiatric Clinic to Telehealth During the COVID-19 Pandemic: A Practice Perspective

Abstract: As the demand for telepsychiatry increases during the COVID-19 pandemic, the strengths and challenges of telepsychiatry implementation must be articulated to improve clinical practices in the long term. Currently, observations within US contexts are lacking; therefore, we report on the rapid implementation of telepsychiatry and workflow experiences in a psychiatric practice based within a large health care system in southeast Texas with a national catchment area. We discuss the logistics of the implementation,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
81
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 75 publications
(96 citation statements)
references
References 37 publications
1
81
0
5
Order By: Relevance
“…Ten articles were included in this scoping review, eight of them identified through database search (published and unpublished sources) [ 2 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ] and two identified through a manual search of websites of MT associations [ 23 , 24 ]. The basic characteristics are in Table 1 and all data-charting tables and a data summary table are in Supplementary S3 .…”
Section: Resultsmentioning
confidence: 99%
“…Ten articles were included in this scoping review, eight of them identified through database search (published and unpublished sources) [ 2 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ] and two identified through a manual search of websites of MT associations [ 23 , 24 ]. The basic characteristics are in Table 1 and all data-charting tables and a data summary table are in Supplementary S3 .…”
Section: Resultsmentioning
confidence: 99%
“…Without much information published on other institutional COVID-19 registries, a direct head-to-head comparison is not feasible. However, CURATOR capitalizes on several unique data sources and currently supports COVID-19 projects across several domains along with work already published from CURATOR data and its associated resources across Houston Methodist [ 7 , 27 - 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite significant efforts to prepare for the rapid expansion, the lack of system integration and established collaborative processes led to escalation of the level of virtual workflow inefficiencies within the program [ 21 ]. While the additional nursing staff helped support the patient caseload, the telemonitoring program was operating under a fragmented ecosystem of virtual technologies (ie, the EMR, the Medly system, videoconferencing) that increased the complexity of clinical practices.…”
Section: Discussionmentioning
confidence: 99%